Microbiological analysis of dental plaque in children with Down syndrome - R. S. Nazarian; O. V. Iskorostenska; T. N. Zamazіy (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Topical focus of modern dentistry is improving the prevention of dental diseases in children with Down syndrome.